Pengaruh Stimulasi Ape Magic Book terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun - Siti Fatimah; Hisbiyatul Hasanah; Ianatuz Zahro (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the effect of using the Magic Book educational teaching aid (APE) on the fine motor development of children aged 4–5 years. This study employed a quantitative approach with a pre-experimental design, specifically a One Group Pretest–Posttest design involving a single group as the research subject. Research that specifically examines the effect of the Magic Book on fine motor skills among children aged 4–5 years is still limited, even though this age range is a critical period for supporting children’s readiness for formal learning activities. The results indicate a significant effect of the use of the Magic Book APE on children’s fine motor skills, as shown by an increase in the pretest mean score (10.60) to the posttest mean score (13.33). The t-test yielded a significance value of 0.000, which is below 0.05, indicating a statistically significant difference. Therefore, the Magic Book APE is proven to have a positive effect on the fine motor development of children aged 4–5 years.